2002
DOI: 10.1017/s0007087402004776
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of ceraunia: archaeology, natural history and the interpretation of prehistoric stone artefacts in the eighteenth century

Abstract: Historians of archaeology have noted that prehistoric stone artefacts were first identified as such during the seventeenth century, and a great deal has been written about the formulation of the idea of a Stone Age in the nineteenth century. Much less attention has been devoted to the study of prehistoric artefacts during the eighteenth century. Yet it was during this time that researchers first began systematically to collect, classify and interpret the cultural and historical meaning of these objects as arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This strikes us as one of the most interesting areas of revision and elaboration revealed by the recent technical analysis to which the panel was subjected (Kemperdick 2018, 143-9). Did Fouquet understand the object he depicted to have been a curious natural phenomenon, potentially a ceraunia (Goodrum 2002;King 1867), or a part of the natural world modified by human hands, or, in a religious vein (Buettner 2022;Honour & Fleming 1982;Robertson & Hutton 2021), a supernatural creation? The former and latter are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This strikes us as one of the most interesting areas of revision and elaboration revealed by the recent technical analysis to which the panel was subjected (Kemperdick 2018, 143-9). Did Fouquet understand the object he depicted to have been a curious natural phenomenon, potentially a ceraunia (Goodrum 2002;King 1867), or a part of the natural world modified by human hands, or, in a religious vein (Buettner 2022;Honour & Fleming 1982;Robertson & Hutton 2021), a supernatural creation? The former and latter are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…From these texts, it is widely stated that prior to the Enlightenment handaxes were often considered to be of natural origin and were thought to have been ‘shot from the clouds’ when lightning struck the ground (King 1867, 77). Sixteenth-century natural historians across Europe noted the presence of ‘ceraunia’ or ‘thunderstones’, which were ‘curiously shaped stone objects … treated as a naturally occurring geological phenomenon’ formed through lightning strikes (Goodrum 2002, 257). This explanation for the presence of handaxes has a long history, with Turner and Wymer (1987) suggesting 44 Roman-deposited Palaeolithic handaxes from Witham, UK, to have been a possible tribute to Jupiter, a Roman god often depicted wielding thunderbolts.…”
Section: The Early Social History Of Handaxesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the presence of stone artifacts in Europe challenged most people's conception of human history and required a rethinking of early human culture. 3 Some archeologists, such as Bernard de Montfaucon (1655-1741) 4 in France and Charles Lyttelton (1714 -1768) 5 in England, even suggested that these artifacts were the earliest evidence of humans on earth and might be extremely old. However, it is important to note that this still meant a human history of only a few thousand years.…”
Section: And the English Geologist Johnmentioning
confidence: 99%
“…Chipped stone tools were for a long time considered as the result of natural processes. Until the 16 th and 17 th centuries, lithic artefacts were characterized as thunderbolts, shaped by the lightning struck, with healing or talismanic powers (Fotiadis 2016, 93;Goodrum 2002). It was during the Renaissance that the first recognition of stone tools as the creation of man was stated by Mercati, a curator of the Vatican collections (Kourtessi-Philippakis 2014b, 113).…”
Section: Lithic Studies In Greece: Research Review Theoretical Trends...mentioning
confidence: 99%